The Implementation of Traditional Games on the Color Recognition Skills of Early Childhood - Nura Lele, Yudit Nida; Erna Budiarti; Nita Priyanti (JURNAL PENA PAUD, 2025)
In this study, the use of traditional games as a learning medium to improve colour recognition skills among 5- to 6-year-old children was examined. The case study was conducted over three months at Taman Kanak Kanak (TK) Negeri Pembina Kanatang in East Sumba, involving 24 purposively selected research participants. The results of this case study confirmed that colour recognition skills in 5- to 6-year-old children can be effectively developed through the implementation of traditional classroom games, such as ‘Porch Stone’, ‘Colored Congklak’, and ‘Colored Jump Rope’. The findings of this case study confirmed that the color recognition skills of the selected children had progressed from the ‘developing’ stage to the ‘well-developed’ stage, and this was evidenced from the feedback of the teachers and mothers of the selected children, who stated that the selected children participated fully and enjoyed the process of playing the traditional games for improved color recognition